Uniformity of thickness of metal sheets by patchwork blanks: potential of adhesive bonding - Gillo Giuliano; Gianluca Parodo; Luca Sorrentino (Fracture and Structural Integrity, 2020)
The sheet metal forming operations generally involve the production of parts characterized by a non-uniform thickness distribution. However, in some cases, a product characterized by a distribution of thicknesses that is as uniform as possible may be desirable. This result can be obtained by using multiphase processes or by subtraction or addition of material from the blank. In this work, which deals with the method for adding material, an innovative methodology has been proposed as an alternative to the welding process. Specifically, the methodology is based on the bonding of a patch (before the deformation process), on the base plate with a constant thickness, in the area that most suffers from the thinning caused by the forming process. In this way, it was possible to influence the deformation of the patchwork blank and its thicknesses distribution. Through finite element analysis, it was possible to study the formability of a patchwork blank by varying the thickness and size of the patch, in order to produce an axially symmetric component by stretching through a hemispherical punch. Preliminary experimental tests demonstrated the reliability of the bonding and the potential of this method to uniform the final thickness of the sheet.